Rajungan Shell (Portunus pelagicus) as Antitoxic Mask Coated with Chitosan Polymer Medium (CPM) For Nicotine Reduction Using Spray Coating Method - Santika Octaviana Putri Br. Purba; Hafidya Norista Pramesti; Nizar Muflih Nuruddin; Nur Laili Alfiatin Mukharomah; Achmad Gufron; Yayok Suryo Purnomo (Future Science, 2022)
Exposure to cigarette smoke in passive smokers has a bad impact because the substances inhaled are 4-6 times greater than the levels inhaled by active smokers. Nicotine is a dangerous substance in cigarettes that can cause respiratory disease. Crab shell waste in Indonesia is very abundant and has a chitin content of 50%-60%. Thus, the purpose of this study was to determine the effectiveness of Rajungan Shell (Portunus pelagicus) as an antitoxic mask coated with Chitosan Polymer Medium (CPM) for nicotine reduction using the spray coating method. Variations in CPM variables were concentrations of 10,000 ppm, 20,000 ppm, 30,000 ppm, 40,000 ppm, and 50,000 ppm with a total of 3 sprays, 5 sprays, and 7 sprays. The results obtained were the degree of deacetylation 69.45%, percent nicotine removal 80.73%, and adsorption capacity of 4,9993 mg/g.